EFFECTIVENESS OF RADIOLOGICAL IMAGING TECHNIQUES (X-RAYS, MDCT, AND MRI) FOR DIAGNOSIS OF PELVIC FISTULA: A SYSTEMATIC REVIEW - Shahzad, M; Anjum, N; Siraj, S; Omer, MA; Shabbir, R; Masood, A (Biological and Clinical Sciences Research Journal, 2021)
This study aimed to evaluate the diagnostic performance of different imaging techniques for preoperative detection of pelvic fistula. Imaging and classification of female genital abnormalities considerably pelvic floor fistulas are significant. We conducted a systematic review of the available literature to highlight the effectiveness of different radiological imaging techniques (X-RAY,U/S,CT,MRI) for the diagnosis of different types of pelvic fistulas to see the limitations of conventional scanning and testing over modern imaging techniques and to show the effectiveness of choosing one imaging modality over other depending upon multiple dynamics e.g., site and types of fistula. The controlled and regular research cases (n= 9) available in English from 2011 to 2020 were included in criteria of research. The evidence databases were used for assessment of certain studies analytically by way of PEDro scale and explicated under decision guidelines. In all relevant articles were identified and included in this systematic review. The radiological techniques showed improved diagnostic performance that established the effectiveness of imaging advancement for administration and treatment of pelvic fistula. Conventional methods have less sensitivity and specificity as compared to modern techniques. X-RAY fistulography and ultrasonography has less sensitivity and specifity as compared to CT scan but still found beneficial in the diagnosis of colovaginal, uterovesical fistula and considered as the most basic clue about the existence of a malignant fistula respectively.it is verified that MDCT is the safer accurate and offered more detailed defects in diagnosis of urogenital, urethrorectal, lower urogenital tract fistulas, upper and middle vaginal fistulas colovesical fistulas(along with X-RAY) and prostate symphyseal fistula(along with MRI).It has been concluded that MRI can access colovesical fistulas inherited vaginal fistulas and prostate symphyseal fistulas(along with CT) more efficiently. It has been concluded that diagnostic imaging for all pelvic fistula is useful, to help the physicians, particularly radiologists, in diagnosis of pelvic fistulas. The choice of imaging technique is dependent upon multiple factors. Advanced medical imaging techniques XRAY,MDCT MRI) are considered more recommended choices as compared to conventional imaging.